The Influence of Zunal-Based Webquest Media on Students’ Digital Literacy in Schools - Rizki Dwi Natasya; Jakfar Shodiq Budiono; Evi Fatimatur Rusydiyah (Program Pascasarjana Universitas Ibrahimy, 2024)
This research aims to determine whether or not there is an influence of using Zunal-based webquest media on students' digital literacy at SMAN 1 Lamongan. This research uses a quantitative approachusing a questionnaire as the main instrument in data collection. The research instrument was created referring to aspects of digital literacy theory according toBeetham Littlejohn and McGill's, who stated that there are 7 important aspects, namely: media literacy, communication and collaboration, learning skills, ICT Literacy, privacy management, digital scholarship, information literacy.Data from the questionnaire results were analyzed using the T test to determine whether there was an influence between the independent variable (webquest media) and the dependent variable (digital literacy). The analysis results show that the significance value (sig) is 0.000, then 0.000 < 0.05, which means Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a very significant influence from the use of webquest media on students' digital literacy at school. This shows that the application of Zunal-based webquests in learning has succeeded in improving students' abilities in using digital technology and accessing information effectively. They have been able to master or at least have an adequate understanding of the use of technology and access to digital information.